On Stable Perturbations of the Generalized Drazin Inverses of Closed Linear Operators in Banach Spaces. (27th September 2012) - Huang, Qianglian; Zhu, Lanping; Chen, Xiaoru; Zhang, Chang
Abstract : We investigate the stable perturbation of the generalized Drazin inverses of closed linear operators in Banach spaces and obtain some new characterizations for the generalized Drazin inverses to have prescribed range and null space. As special cases of our results, we recover the perturbation theorems of Wei and Wang, Castro and Koliha, Rakocevic and Wei, Castro and Koliha and Wei.